P058 Design and performance of the alinity m STI assay for the detection of CT, NG, TV, and MG. (14th July 2019) - Nelson, Kevin; Joseph, Ajith; Wiesneth, Russ; Lander, Rachel; Hwang, Dick; Jacobson, Chris; Lennon, Frances; Touw, Ketrija; Zhang, Qingbei; Toonen, Joseph; Connors, Alanna; Patel, Jinal; et al.
Abstract : Background: The Alinity m STI assay is an in vitro assay for the qualitative detection of nucleic acids from Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis, and Mycoplasma genitalium (MG) for use on the automated Alinity m System. For CT, NG, and TV, the assay may be used to test endocervical swabs, clinician-collected and self-collected vaginal swabs, gynecological specimens in PreservCyt, female urine, and male urine from symptomatic and asymptomatic individuals. For MG, the assay may be used to test endocervical swabs from symptomatic and asymptomatic individuals. Methods: The Alinity m STI assay is designed for the Alinity m System, a fully automated continuous access analyzer that utilizes magnetic microparticle sample preparation chemistry, unit-dose lyophilized amplification reagents, and ReadiFlex TM processing logistics to deliver a time-to-first-result of 115 minutes. The assay can be customized to report any combination of CT, NG, TV, or MG from a single test to allow flexibility in the management of laboratory testing. In addition to CT, NG, TV and MG, the assay detects an endogenous human DNA sequence and an exogenous internal control as validity controls for sample adequacy, extraction, and amplification efficiency. Results: Performance characteristics of the Alinity m STI assay were evaluated in a clinical study. Endocervical swabs, vaginal swabs, gynecological specimens in PreservCyt, and urine were collected from 398 females. Urine was collected from 411 males. For each subject, the Alinity specimen type was compared to a matched specimen tested with CE marked assays for CT, NG, TV, and MG. For all analytes, the overall positive percent agreement ranged from 91.4% to 98.2% and the overall negative percent agreement ranged from 99.7% to 100%. Conclusion: The Alinity m STI assay is a sensitive and specific assay for the detection and differentiation of CT, NG, TV, and MG on a state-of-the-art instrument. Disclosure: No significant relationships.